Investigating white matter connectomes in amnestic and non‐amnestic Alzheimer's disease clinical variants. (31st December 2021) - Bharne, Pandurang R.; Kinney, Nikolas G.; Da Re, Fulvio; Spotorno, Nicola; Olm, Christopher A.; Cook, Philip; Irwin, David J.; McMillan, Corey T.; Grossman, Murray; Phillips, Jeffrey S.
Abstract: Background: Recent models propose that spread of Alzheimer's disease (AD) pathology may be mediated by white matter connectivity. AD clinical variants exhibit partially distinct patterns of gray matter atrophy. However, it is less clear whether phenotypic differences extend to patients' white matter connectomes. We hypothesized that white matter connectivity would differ between healthy controls, amnestic AD (aAD), and non‐amnestic AD (naAD), including behavioral variant Alzheimer's disease (bvAD), logopenic‐variant primary progressive aphasia (lvPPA), and posterior cortical atrophy (PCA). Method: We examined white matter connectomes in 194 participants (controls=60, aAD=42, bvAD=25, lvPPA=39, PCA=28). All participants with dementia had evidence of AD pathologic change based on autopsy, Aβ1–42 from cerebrospinal fluid, or [18] F‐florbetaben positron emission tomography. T1‐weighted and diffusion tensor images were collected using a 3 Tesla scanner. We calculated gray matter volume for cortical regions of interest and median fractional anisotropy (FA) for the tract connecting every pair of regions. Tracts with the most variable FA values across participants were excluded to yield graphs with 30% density. Linear regressions adjusted for sex and age were used to investigate group differences in degree and betweenness centrality as well as the relationship between gray matter volume and FA measures. Phenotypic differences in tractwise FA were evaluated using t‐tests. Result: Both node and edge metrics indicated significant (p<.05, corrected) widespread differences between patient groups and controls. In contrasts between disease groups, aAD patients had reduced degree in multiple occipital and inferior temporal regions; and higher betweenness centrality in bilateral frontal and parietal regions relative to naAD phenotypes. Tractwise FA values did not differ between patient groups. Across groups, endpoint gray matter volume was correlated with tractwise FA measures. Conclusion: Both node‐ and edge‐based metrics suggested patients' white matter connectomes exhibited degeneration relative to controls. Phenotypic differences between patient populations were few, suggesting that AD clinical variants with distinct patterns of gray matter disease nevertheless had broadly similar patterns of white matter degeneration. Gray matter atrophy was closely associated with lower values of FA of white matter tracts connecting atrophied regions, consistent with Wallerian degeneration of white matter.